Prevalence and Onset of Hepatotoxicity Caused by Anti-Tuberculosis Drugs on Pulmonary TB Patients in Wangaya General Hospital Denpasar – Bali in 2016 - Wayan Evie Frida Yustin; Ida Ayu Jasminarti Dwi Kusumawardani; Ni Wayan Candrawati; Ida Bagus Ngurah Rai (Universitas Baiturrahmah, 2022)
Introduction: As tuberculosis (TB) endemic country, TB becomes a community health problem in Indonesia. Data from the Global TB Report in 2016 showed that Indonesia is the second most country with TB burden after India. WHO and the Ministry of Health issue a TB prevention program based on the End TB Strategy aimed to reduce morbidity, mortality, and disability due to TB. One of the challenges faced in the management of TB is the side effects of the anti-tuberculosis drug. Hepatotoxicity is the most common side effect. Aims: This study aims to determine the prevalence and onset of anti-TB drug-induced hepatotoxicity in TB patients after receiving the anti-TB drug in Wangaya Hospital Denpasar Bali. Method: This study used a cross-sectional method by obtaining secondary data of pulmonary TB patients visiting the pulmonary clinic in Wangaya General Hospital from January to December 2016. Result: Of 77 subjects, fifty-six percent of them were men. The highest prevalence was found in the 41-50 years age group (26.9%), while the lowest was found in the 81-90 years age group (1.2%). Anti-TB drug-induced hepatotoxicity occurred in 6.5% of subjects. The most frequent onset of hepatotoxicity occurred within the second week of medication. Anti-TB drug-induced hepatotoxicity occurred in 6.5% of subjects. The most frequent onset of hepatotoxicity occurred within the second week of medication. Conclusion: Based on this study, we suggest a liver function test before and after two weeks of an anti-TB drug.